MENGHITUNG EFISIENSI MILL FAN YANG TERDAPAT DI PABRIK BATURAJA II PT SEMEN BATURAJA (Persero) Tbk. PADA PROSES CEMENT MILL YANG DITINJAU DARI PEMAKAIAN ARUS LISTRIK - Hidayat, M. Taufik; Anugrah, Rendotian; Safaruddin, Safaruddin (Jurnal Multidisipliner Bharasumba, 2022)
PT Semen Baturaja (Persero) Tbk, is a company that produces cement located in several areas on the island of South Sumatra and one of its largest factories is located in the Baturaja area, Ogan Komering Ulu. PT Semen Baturaja has several stages, namely: the mining process, the grinding and drying process of raw materials, the raw meal burning process, the clinker grinding process, and the cement bagging process. At the stage of grinding the clinker occurs in the cement mill. The cement mill tool is assisted by a mill fan which functions to generate air flow in the mill air flow system so that the milling process, moisture reduction, separation, and material transport take place perfectly. To find out and ensure the performance of the operating tool, namely the mill fan, is functioning properly, an efficiency calculation is carried out. The calculation of mill fan efficiency obtained from 10 consecutive days of data from the Central Control Room (CCR) is 77.580%; 77.741%; 78.780%; 86.457%; 81.893%; 79.238%; 76.255%; 78.078%; 77.460%, 75.497%. The increase and decrease in efficiency is caused by the difference in the amount of cement production each day and the low impeller speed.